The Role of Education and Challenges of the Implementation of the Rebozo Technique in Midwifery Practice: A Scoping Review - Aprianti, Nurul Azmi; Mose, Johanes Cornelius; Pratiwi, Yuni Susanti; Susiarno, Hadi; Dany Hilmanto; Irianti, Setyorini (JTP - Jurnal Teknologi Pendidikan, 2025)
The Rebozo technique is a non-pharmacological method that is effective in supporting the delivery process. This research aims to explore the benefits, implementation challenges, and role of education in the application of this technique. The study was conducted through a scoping review of 19 selected articles and analyzed thematically based on certain inclusion criteria from various international databases. The results showed that the Rebozo technique improved maternal comfort, reduced the need for medical intervention, and supported a positive childbirth experience. The main obstacles include a lack of training and limited facilities. Structured education and training for health workers, as well as couple education to support mothers during childbirth, are important elements in the optimization of this technique. Research recommendations include practice-based training for health workers and strengthening the role of couples through educational programs to support the implementation of the Rebozo technique in physiological childbirth services.